Congenital internal rotation deformity of the distal femur presenting as patellofemoral instability and pain. Issue 2 (18th April 2019) - Zhang, Xinyuan; Attenello, John; Safran, Marc R; Lowenberg, David W
Abstract : Objectives: Femoral antetorsion, defined as the angle of rotation of the femoral head and neck axis in relation to the transcondylar axis of the distal femur, is a cause for patellofemoral instability and anterior knee pain. Most clinical reports do not distinguish between antetorsion of the femur distal to the isthmus and anteversion of the proximal femur, which is another cause of femoral internal rotational deformity. Methods: This retrospective observational case series evaluated four cases in three female patients who underwent evaluation of surgical intervention for chronic anterior knee pain since childhood. Physical examination and radiographic images supported the diagnosis of internal rotation deformity at the distal femora in all four cases. Distal femoral derotational osteotomy of 45°, 60° and 30° were performed, respectively. Kujala scoring system for patellofemoral pathology was used to assess the change in knee symptoms before and after the osteotomies. Results: This study demonstrated successful treatment of the resultant knee symptoms from femoral antetorsion with distal femur derotational osteotomy in all three patients. Conclusions: Patellofemoral syndrome is multifactorial, and the true anatomic reason for each patient's individual pathology must be determined before surgery proceeds. Level of evidence: Level V.